2013
DOI: 10.1038/ncomms3106
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization dampens influenza-mediated acute lung injury via induction of M2 alveolar macrophages

Abstract: While the presence of airway bacteria is known to be associated with improved immunity against influenza virus, the mechanism by which endogenous microbiota influence antiviral immunity remains unclear. Here we show that specific pathogen-free mice are more sensitive to influenza-mediated death than mice living in a natural environment. Priming with Toll-like receptor 2-ligand+ Staphylococcus aureus, which commonly colonizes the upper respiratory mucosa, significantly attenuates influenza-mediated lung immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
168
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(181 citation statements)
references
References 46 publications
5
168
1
4
Order By: Relevance
“…Whilst these studies were carried out with BMDMs rather than alveolar macrophages, they provide important clues for understanding the function of macrophages in control of influenza virus infections. Wang et al (2013) recently showed that alternatively activated alveolar macrophages can protect against lethal challenge in a mouse model. Their study did not address macrophage infection, but our data would suggest that infection of alternatively activated macrophages per se is likely to play a role in this protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst these studies were carried out with BMDMs rather than alveolar macrophages, they provide important clues for understanding the function of macrophages in control of influenza virus infections. Wang et al (2013) recently showed that alternatively activated alveolar macrophages can protect against lethal challenge in a mouse model. Their study did not address macrophage infection, but our data would suggest that infection of alternatively activated macrophages per se is likely to play a role in this protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we chose Staphylococcus aureus, a common commensal bacterium in the upper respiratory tract, to build a mouse model of bacterial preinfection and found that it dampened the subsequent influenza-induced "cytokine storm" through a mechanism involving the induction of the immuneinhibitory M2 macrophage cells (16). In this S. aureus preinfection model, the most optimal protective effect occurred when mice were infected with S. aureus 3 d before PR8 infection; if mice were infected with S. aureus 7 d before PR8 infection, the protective effect was weakened.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of total protein, cytokines, and Igs in bronchoalveolar lavage fluid or serum Bronchoalveolar lavage fluid (BALF) was collected as previously described (16). In brief, the lungs were washed once with 1 ml sterile saline through an intratracheal cannula.…”
Section: Mouse Infectionsmentioning
confidence: 99%
“…Treatment of mice with this bacterium before influenza inoculation reduced lung damage during influenza infection. Mechanistically, this protection was due to the recruitment of monocytes from the blood, which subsequently differentiated into anti‐inflammatory M2 alveolar macrophages in the lung 65. These macrophages inhibit the recruitment of excessive inflammatory cells during infection and it is thought that this reduces tissue damage and mortality caused by influenza.…”
Section: Host Resistance To Airway Infection and The Microbiotamentioning
confidence: 99%